Generation of a genetically encoded voltage indicator MARINA reporter human iPS cell line using Cas9 (VULSCi002-A-2) - Aistė Petruškevičiūtė; Ugnė Šimuliūnaitė; Catalina M. Polanco; Barbara Rojas; Simonas Kuras; Beatričė Valatkaitė-Rakštienė; Rimvydas Norvilas; Akshay Kumar Vijaya; Patricia Muñoz; Urtė Neniškytė; Artūras Jakubauskas; Aurelijus Burokas; et al. (Stem Cell Research)
Fluorescent protein-based Genetically Encoded Voltage Indicators (GEVI) offer a remarkable system for high-throughput screening of membrane potential phenotypes. The GEVI MARINA is a derivative from ArcLight, which conversely to ArcLight increases its fluorescence intensity alongside depolarization. Here we created knock-in reporter human iPS cell lines carrying the MARINA reporter using SpCas9 programmable nuclease and characterize a heterozygous clone.